Reactions to Intergroup Competition Under Win-Lose Conditions - Blake, Robert R.; Mouton, Jane Srygley (Management Science, 1961)
Findings from investigations concerning the dynamics of intergroup competition under win-lose conditions are summarized first. The second step is to demonstrate, by presenting a synopsis of a real case, how these findings can be applied in converting a situation of management-union conflict into one of collaboration. The conclusion is that the industrial ethic which causes groups to interact with one another on a competitive win-lose basis, must and can be replaced by the new ethic which makes it possible for groups to approach their differences in points of view from a problem-solving orientation based on openness and reinforced by mutual respect and trust.